On the Copper(I)-Catalyzed Cross-Coupling of 1-Bromoalkynes with N-Heterocyclic Organozinc Reagents: Substrate Scope and Catalyst Evaluation - Frabitore, Christian; Livinghouse, Tom (Synthesis, 2023)
Nitrogen-containing heterocycles are ubiquitous in FDA-approved small molecule pharmaceuticals. Herein, we expand on a novel synthetic method for the production of saturated N-heterocyclic pharmacophore motifs with an internal alkyne for elaboration. The treatment of N,N-dimethylhydrazinoalkenes with diethylzinc followed by a Cu(I)-catalyzed cross-coupling with 1-bromoalkynes affords piperidines and pyrrolidines in respectable yields. Functional group tolerance is demonstrated by the inclusion of heteroatom-bearing alkynes. Unexpectedly, the use of ethyl propiolate as the trapping electrophile led to selective N-functionalization with the formation of vinylogous urethanes. Alternative Cu(I) complexes were also evaluated as prospective catalysts. This synthetic protocol can readily be achieved on a preparative scale.
Keywords: cross-coupling; copper; catalysis; heterocycles; alkynes